1996
DOI: 10.1037/0894-4105.10.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in visual evoked potential estimates on interhemishperic transfer.

Abstract: Twenty-six younger (ages 18-36 years) and 19 older (ages 60-88 years) healthy right-handed men and women were tested for interhemispheric transfer by using visual evoked potentials to laterally presented checkerboards. Interhemispheric transfer time (IHTT) was estimated by subtracting latencies for both P100 and N160 peaks of the waveform contralateral to the stimulus from the waveform ipsilateral to the stimulus for homologous sites. The quality of interhemispheric transfer was estimated by comparing peak-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Previous research investigating the CUD in healthy older adults have reported equivocal results; some studies have demonstrated significant increases in the magnitude of the CUD compared to younger adults (Jeeves & Moes, 1996;Reuter-Lorenz & Stanczak, 2000;Schulte et al, 2004;Schulte et al, 2005), while others have found no such effect (Hoptman, Davidson, Gudmundsson, Schreiber, & Ershler, 1996). The validity of the CUD as an index of callosal transmission time has been called into question by studies in which only approximately between half to two thirds of participants showed positive CUDs, suggesting that the simple anatomical model on which the CUD is based may be invalid (Saron & Davidson, 1989;Davidson, Leslie, & Saron, 1990).…”
Section: The Crossed-uncrossed Differencementioning
confidence: 92%
See 1 more Smart Citation
“…Previous research investigating the CUD in healthy older adults have reported equivocal results; some studies have demonstrated significant increases in the magnitude of the CUD compared to younger adults (Jeeves & Moes, 1996;Reuter-Lorenz & Stanczak, 2000;Schulte et al, 2004;Schulte et al, 2005), while others have found no such effect (Hoptman, Davidson, Gudmundsson, Schreiber, & Ershler, 1996). The validity of the CUD as an index of callosal transmission time has been called into question by studies in which only approximately between half to two thirds of participants showed positive CUDs, suggesting that the simple anatomical model on which the CUD is based may be invalid (Saron & Davidson, 1989;Davidson, Leslie, & Saron, 1990).…”
Section: The Crossed-uncrossed Differencementioning
confidence: 92%
“…The role of the corpus callosum in mediating the CUD has gained support from the findings that the CUD increases dramatically, often to around 70 ms, in patients who have had partial or complete callosotomies and those with callosal agenesis, although there are considerable individual differences (Corballis et al, 2003;Roser & Corballis, 2002;Roser & Corballis, 2003). Previous research investigating the CUD in healthy older adults have reported equivocal results; some studies have demonstrated significant increases in the magnitude of the CUD compared to younger adults (Jeeves & Moes, 1996;Reuter-Lorenz & Stanczak, 2000;Schulte et al, 2004;Schulte et al, 2005), while others have found no such effect (Hoptman, Davidson, Gudmundsson, Schreiber, & Ershler, 1996). The validity of the CUD as an index of callosal transmission time has been called into question by studies in which only approximately between half to two thirds of participants showed positive CUDs, suggesting that the simple anatomical model on which the CUD is based may be invalid (Saron & Davidson, 1989;Davidson, Leslie, & Saron, 1990).…”
Section: The Crossed-uncrossed Differencementioning
confidence: 99%
“…Recent work by Jeeves and Moes (1996) showed that healthy adults between the ages of 60 and 82 years show a significant increase in the magnitude of the CUD compared to younger adults. Typically, the early components of the ERPs, such as the P100, are smaller in the hemisphere ipsilateral to the stimulated visual field (crossed condition) compared to those recorded from the contralateral hemisphere (uncrossed condition; for a review, see Hoptman et al, 1996). Their ERP measures of sensorimotor events were more revealing, however.…”
Section: Aging and Sensorimotor Transfermentioning
confidence: 99%
“…Several studies indicate that the CUD is affected in older adults (Jeeves and Moes, 1996; Reuter-Lorenz and Stanczak, 2000; Schulte et al, 2004). Although not all studies could find an increase in the magnitude of the CUD in older adults (Hoptman et al, 1996), recent DTI studies have revealed correlations between subtle variations in regional white matter callosal microstructure and behavioral measures of interhemispheric transfer time and cognitive ability (Muetzel et al, 2008; Sullivan et al, 2010; Wolf et al, 2012). Fractional anisotropy (FA), an index of white matter fiber integrity, of anterior callosal regions is lower than in posterior regions and typically decreases disproportionally with advancing age (region of interest analyses: Pfefferbaum and Sullivan, 2003; Pfefferbaum et al, 2000, 2005; Salat et al, 2005; fiber tracking analyses: Stadlbauer et al, 2008; Sullivan et al, 2006, 2010; Zahr et al, 2009; stereology in postmortem human brains: Hou and Pakkenberg, 2011).…”
Section: Introductionmentioning
confidence: 99%